Pemanfaatan Video Edukatif untuk Memahami Uang dan Transaksi Digital: Studi Literatur - Widia Gultom; Primawati Sinaga; Depina Tumangger (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The rapid advancement of financial technology has accelerated the transition of payment systems from cash-based transactions to a digital ecosystem involving e-wallets, QRIS, and mobile banking services. Although this transformation offers greater convenience and economic efficiency, it simultaneously creates critical challenges regarding low digital financial literacy, particularly among the younger generation. This study aims to analyze the effectiveness of utilizing educational videos to improve public conceptual understanding of money and digital transactions. The research employed a literature review method with an integrative qualitative approach to synthesize prior studies on digital financial literacy, audiovisual learning media, and digital transaction behavior. The findings indicate that audiovisual educational videos, particularly in short-form or micro-learning formats, are highly effective in enhancing public understanding of digital transaction concepts compared to conventional learning methods. This approach is considered highly compatible with the learning characteristics of the digital generation, which are inherently interactive, visually engaging, and dependent on social media platforms such as YouTube and TikTok. However, its effectiveness is still contingent upon the quality of instructional design, information validity, and users’ basic digital literacy levels. Consequently, educational videos can be optimized as a strategic instrument to accelerate digital financial literacy in the era of modern economic transformation.